THE ANALYSIS OF 4th GRADE STUDENT TEXTBOOK BASED ON THE 2013 CURRICULUM ON THE THEME OF PAHLAWANKU WITH THE SUBTHEME OF PERJUANGAN PARA PAHLAWAN (LESSON SIX) - Bernadine Ajeng Indriasari; Bambang Afriadi (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
The purpose of this research is to determine suitability of stundent book of fourth grade student based on Curricullum 2013 on theme “Pahlawanku” subtheme “Perjuangan Para Pahlawan” on lesson six with core competencies, learning objectives, indicator, learning activity, materials, tools and learning resources. This section is the sixth fragmen of eighteen analyze of learning activities plan in student book grade fourth based Curicullum 2013. Research method is descriptive qualitative method by analyzing documents are student book of fourth grade student based on Curricullum 2013 on theme “Pahlawanku” subtheme “Perjuangan Para Pahlawan” on lesson six and teacher book of fourth grade student based on Curricullum 2013 on theme “Pahlawanku” subtheme “Perjuangan para Pahlawan” on lesson six. The analize revolves on the rule of Menteri Pendidikan dan Kebudayaan Nasional, an article discussing about the implementation of Curricullum 2013 and article from website of Badan Nasional Standar Pendidikan (BSNP). Based on result of this research are found that core competencies of mathematics that do not appear in the competency mapping appear in learning materials, indicators of IPA do not match the needed of basic competencies, learning objectives that are not in accordance with the formulation of indicators, materials of IPA and PJOK subjects to liltte and learning subject and tools not listed in student books. Based on the results of the analysis it was conclude that student book of fourth grade student theme “Pahlawanku” subtheme “Perjuangan Para Pahlawan” on lesson six needs a lot of improvement in accordance with the study result.